Assessing the H-Indexes of Editorial Board Members in Ophthalmology Journals Published in Türkiye - Erdag, Murat; Citirik, Mehmet (Kare Publ, 2024)
Objectives: The focus of this study was to assess and compare the h-indexes of editorial board members from eight ophthalmology journals in T & uuml;rkiye and explore the potential correlations between these indexes and the sub-specialties of board members. Methods: Conducted in December 2023, this cross-sectional study utilized publicly available data from Google Scholar (GS), Web of Science, and Scopus. The h-index and number of publications by editorial board members from eight Turkish ophthalmology journals were analyzed. Statistical analysis for this study involved the use of SPSS, employing descriptive statistics, one-way analysis of variance, and post hoc tests for group comparisons. Results: Of the 415 editorial board members, 26 were not ophthalmologists and 12 worked abroad; the credentials of 10 could not be verified. A total of 367 authors were evaluated, revealing significant differences in publication numbers and h-indices among the different subspecialties. Notably, the retinal specialists demonstrated higher productivity. Variability in citation counts was observed across databases, with GS having the widest range. Differences were also noted in the publication and h-index among the editorial boards of different journals. Conclusion: The h-index and number of publications effectively reflected the active status of ophthalmology authors. This study contributes valuable information regarding Turkish ophthalmology journals and their editorial boards, serving as an inspiration for young ophthalmologists. These findings underscore the diverse successes of ophthalmologists across subspecialties, encouraging the exploration of less-explored areas in academic pursuits.
Keywords: Editorial board members; H -indexes; ophthalmology journals; T & uuml;rkiye